INDEKS MASA TUBUH DENGAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS TIPE 2 - Yuswatiningsih, Endang; Nofalia, Ifa (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
High blood glucose levels are caused by insufficient insulin produced by the pancreas, causing hyperglycemia. The purpose of this study was to analyze the relationship between body mass index and blood sugar levels during type 2 diabetes mellitus. This type of research was correlational analysis with a cross-sectional approach. The population of this study was all type 2 diabetes mellitus patients at the Melati Elderly Posyandu, Mlaras Village, Sumobito as many as 54 respondents. The sample of this study was 48 respondents with type 2 diabetes mellitus at the Melati Elderly Posyandu, Mlaras Village, Sumobito using the Slovin formula. The sampling technique is simple random sampling. Body mass index variable data was collected by measuring body weight and height and calculated using the formula BMI = BB/TB2(m) while blood sugar levels were variable using a 5010 V5+ photometer. Data processing by editing, coding, scoring, tabulating and data analysis using the Pearson correlation statistical test with an error rate (alpha) of 0.05. Before the Pearson correlation test was carried out, the data normality test was carried out with the Kolmogorov-Smirnov test because it uses a ratio data scale. The results showed that the average body mass index was 19.18 with a standard deviation of 4.14 while the blood glucose level at the time was 197.25 with a standard deviation of 60.62. The data normality test is fulfilled. The results of the Pearson correlation test showed that the value of p = 0.025 was smaller than alpha 0.05, so H1 was accepted. The conclusion of this study is that there is a relationship between body mass index and blood glucose levels in patients with type 2 diabetes mellitus. It is hoped that health workers will always provide information related to risk factors for type 2 diabetes mellitus.